Risk of COVID-19 infection, hospitalization and mortality in psoriasis patients treated with interleukin-17 inhibitors: A systematic review and meta-analysis - Liu, Meitong; Wang, Huijuan; Liu, Lu; Cui, Saijin; Huo, Xiangran; Xiao, Zhuoyun; Zhao, Yaning; Wang, Bin; Zhang, Guoqiang; Wang, Na (Frontiers in Immunology, 2022)
Background Coronavirus disease 2019 (COVID-19) have brought great disaster to mankind, and there is currently no globally recognized specific drug or treatment. Severe COVID-19 may trigger a cytokine storm, manifested by increased levels of cytokines including interleukin-17 (IL-17), so a new strategy to treat COVID-19 may be to use existing IL-17 inhibitors, which have demonstrated efficacy, safety and tolerability in the treatment of psoriasis. However, the use of IL-17 inhibitors in patients with psoriasis during the COVID-19 pandemic remains controversial due to reports that IL-17 inhibitors may increase the risk of respiratory tract infections. Objectives The systematic review and meta-analysis aimed to evaluate the effect of IL-17 inhibitors on the risk of COVID-19 infection, hospitalization, and mortality in patients with psoriasis. Methods Databases (including Embase, PubMed, SCI-Web of Science, Scopus, CNKI, and the Cochrane Library) were searched up to August 23, 2022, for studies exploring differences in COVID-19 outcomes between psoriasis patients using IL-17 inhibitors and those using non-biologics. Two authors independently extracted data and assessed the risk of bias in a double-blind manner. The risk ratios (RRs) and 95% confidence intervals (CIs) were calculated and heterogeneities were determined by the Q test and I2 statistic. And the numbers needed to treat (NNTs) were calculated to assess the clinical value of IL-17 inhibitors in preventing SARS-CoV-2 infection and treating COVID-19. Results Nine observational studies involving 7,106 participants were included. The pooled effect showed no significant differences in the rates of SARS-CoV-2 infection (P = 0.94; I2 = 19.5%), COVID-19 hospitalization (P = 0.64; I2 = 0.0%), and COVID-19 mortality (P = 0.32; I2 = 0.0%) in psoriasis patients using IL-17 inhibitors compared with using non-biologics. Subgroup analyses grouped by age and COVID-19 cases, respectively, revealed consistent results as above. Meanwhile, the pooled NNTs showed no significant differences between the two groups in the clinical value of preventing SARS-CoV-2 infection and treating COVID-19. Conclusion The use of IL-17 inhibitors in patients with psoriasis does not increase the risk of SARS-CoV-2 infection or worsen the course of COVID-19. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022335195.